2008
DOI: 10.1111/j.1365-2702.2008.02639.x
|View full text |Cite
|
Sign up to set email alerts
|

Poor work environments and nurse inexperience are associated with burnout, job dissatisfaction and quality deficits in Japanese hospitals

Abstract: Aims. To describe nurse burnout, job dissatisfaction and quality of care in Japanese hospitals and to determine how these outcomes are associated with work environment factors. Background. Nurse burnout and job dissatisfaction are associated with poor nurse retention and uneven quality of care in other countries but comprehensive data have been lacking on Japan. Design. Cross-sectional survey of 5956 staff nurses on 302 units in 19 acute hospitals in Japan. Methods. Nurses were provided information about years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
138
1
19

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(169 citation statements)
references
References 15 publications
(22 reference statements)
11
138
1
19
Order By: Relevance
“…The unrelenting rise in patient acuity (Milisen et al, 2006) was also mentioned in relation to quality. Inpatients have shorter stays and their care is more intensive (Kanai-Pak et al, 2008). Inpatients presenting with increased clinical complexity and greater acuity have significant repercussions for hospital staff.…”
Section: Resultsmentioning
confidence: 99%
“…The unrelenting rise in patient acuity (Milisen et al, 2006) was also mentioned in relation to quality. Inpatients have shorter stays and their care is more intensive (Kanai-Pak et al, 2008). Inpatients presenting with increased clinical complexity and greater acuity have significant repercussions for hospital staff.…”
Section: Resultsmentioning
confidence: 99%
“…These results are consistent with those of other studies which suggest that higher levels of stress are found in inexperienced younger nurses. [53,54] Furthermore, the studies indicated that working conditions together with shift schedules were accountable for the development of burnout especially among female shift-working nurses. [55,56] Therefore, the development of a stress reduction policy in the healthcare organizations that aims to identify work related stress and to prevent it by providing an educational strategy is a crucial issue.…”
Section: Discussionmentioning
confidence: 99%
“…[12] On the other hand, conditions of career advancement for nurses could not be provided without nursing managers' support in the working environment. [16,17] Nursing managers confront with two challenges: maintaining experienced nurses and developing healthy working environment. [11] Kramer et al believe that nursing managers develop indices of nurses' working environment through providing optimal working environment and developing meaningful work with expertise knowledge.…”
Section: Introductionmentioning
confidence: 99%